Comparing Probing-Prompting and Problem-Based Learning to Improve Mathematical Reasoning, Self-Efficacy, and Adversity Quotient in Junior High Students - Sophia Elma; Elly Arliani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing students’ mathematical reasoning, self-efficacy, and adversity quotient is essential in supporting their academic resilience and problem-solving skills. This study compares the effectiveness of Probing-Prompting (PP) and Problem-Based Learning (PBL) models in enhancing these three domains among junior high school students. A quasi-experimental design with a nonequivalent (pretest-posttest) control-group approach was used. The study involved 56 seventh-grade students from a public junior high school in Yogyakarta, divided into two classes: an experimental group using PP and a control group using PBL. Data were collected using validated and reliable instruments, including mathematical reasoning tests and self-report questionnaires on self-efficacy and adversity quotient. Data analysis employed paired t-tests, independent t-tests, Mann–Whitney U tests, and Hotelling's T² with a significance level of 0.05. Both PP and PBL significantly improved students' mathematical reasoning, self-efficacy, and adversity quotient. However, comparative analyses showed no statistically significant differences in the mean gain scores between the two groups for all three variables: mathematical reasoning (t = 0.829, p = 0.206), self-efficacy (U = 351.50, p = 0.256), and adversity quotient (U = 334.00, p = 0.173). While PP and PBL are both effective, neither demonstrated clear superiority in improving the targeted skills. The short intervention period may have limited the full impact of the PP model. Nonetheless, the findings suggest both models offer valuable strategies for supporting students’ cognitive and non-cognitive development.